PERFORMANCE CHARACTERISTIC OF FLUIDIZED BED GASIFICATION USING LOW RANK COAL AND BIOMASS MIXING FUEL - Priambodo, Trisaksono B; K.Pasya, Mustafa; R.Hoetman, Agus (Agency for the Assessment and Application of Technology)
The paper describes the fundamental gasification characteristic of biomass and low rank coal mixture in gasification process using co-gasification methods as mixed fuel in fluidized bed gasifier furnace. The experiments focused in getting quality of gas produced from gasification processes of rice husks and low rank coal. The experiment on rice husks gasification found that every given fuel flow rate, the air fuel ratio increases with the rising of bed temperature. Higher operating temperatures lead to the lower heating values of gas product. More fuel needed to be burnt in order to attain higher temperature of the bed, however, the increase of operating temperature will increase in the efficiency of gasificationof rural society in development of PLTM/H to support rural electricity will work successfully.